The Brazilian 'Tax War' The Case of Value-Added Tax Competition among the States - de Mello, Luiz (OECD Economics Department Working Papers, 2007)
This paper tests for horizontal tax competition in the VAT for a sample of Brazilian states in the period 1985-2001. The states have considerable autonomy to set their VAT rates and bases, often using this tax as an industrial policy tool. The empirical findings, based on the estimation of a tax reaction function in an error-correction set-up, confirm the hypothesis of horizontal tax competition: the states react strongly to changes in their neighbours? VAT code, especially those that belong to the same geo-economic region. Also, there appears to be a Stackelberg leader among the states, with the remaining jurisdictions responding strongly to its policy moves. There is no co-occupancy of tax bases between different levels of government and hence limited scope for vertical externalities in tax setting. But the fact that the federal government shares with the states part of the revenue of its more elastic taxes, such as the income tax, appears to affect the opportunity cost of horizontal tax competition